SISTEM INFORMASI KEARSIPAN SURAT DAN PROPOSAL BERBASIS WEBSITE - Rizal Rachman; Maulana Ardiansyah; En Tay (STMIK Mardira Indonesia, Bandung, 2022)
The development of technology increases rapidly along with the times. Archiving is something that cannot be separated from an organization or institution, archives have such an important role. the number of letters created and received administratively, so that the search data is inefficient in terms of time and energy using a manual system. So at this time needed a letter management administration system that is more structured to speed up the search for existing data and make reports, So the author makes an archive application that is considered necessary and helps Baznas. This application is designed using PHP and Mysql. Because it is web-based, this archive application has the ability, can be accessed anywhere, the admin can manage with user logins so that it can facilitate, install, save and save letters and proposals in or out, print reports. Archiving letters and proposals that used to be manual are now digital. Keywords: Information systems, mail archieve, PHP, Mysql